Evolution of specific 3 `-5 `-linkages in RNA in pre-biotic soup: a new hypothesis - Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2016)
This article reviews the different possibilities towards progression of the formation of DNA/RNA in the chemical world, before life, in enzyme-free conditions. The advent of deoxyribo- and ribopentose-sugars, nucleosides, nucleotides and oligonucleotides in the prebiotic soup is briefly discussed. Further, the formation of early single stranded oligomers, base-pairing possibilities and information transfer based on the stability parameters of the derived duplexes is reviewed. Each theory has its own merits and demerits which we have elaborated upon. Lastly, using clues from this literature, a possible explanation for the specific 3'-5'-linkages in RNA is proposed.